Modelling glacier fluctuations in the Soer Rondane, Dronning Maud Land, Antarctica - Pattyn, F.; Huybrechts, Philippe; Decleir, H. (1989)
Morainic deposits found above the present glacier surface in the central Sor Rondane Mountains give evidence of former glaciations. In this paper, an attemptis made to interprete these observed glacier fluctuations in terms of environmental change. To do this, a numerical flowline model, taking into accountthermodynamics and a coupled ice shelf, has been developed and is applied to two outlet glaciers through the mountain range, Gunnestadbreen andJenningsbreen. It is found that lower ice temperatures accompagned by a reduced accumulation, further enhanced by a drop in sea level corresponding totypical glacial conditions account for a 150 - 200 m rise in glacier level. From a comparison of these results with palaeogeographical reconstruction for a'maximum' glacial stage for Jenningsbreen by Hirakawa et al. (1989) it is argued that their morainic deposits relate to an earlier Cenozoic glaciation involvinga full grown ice sheet.